Ihre Waffe war der Zeichenstift. Vorstellung der durch den DAB geförderten Arbeit „Die junge Käthe Kollwitz in ihrer künstlerischen Findungsphase" - Schreckenberg, Carolin (Deutscher Akademikerinnenbund e.V.-Newsletter Juni)

Im Todeswasser: Eine Metapher in der Hebräischen Bibel und im Werbespot ‚Der Weg‘ - Bergmann, Claudia Dorit (Weihnachts-Werbespots als moderne Krippenspiele)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Immersive Smart Home Planning and Automation with Mixed Reality and Digital Twin Technologies - Yigitbas, Enes; Karch, Julian (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)

Impact of non-rotationally symmetric joint orientation on neighbouring joints and component performance in lap shear specimens - Devulapally, Deekshith Reddy; Steinfelder, Christian; Tröster, Thomas; Brosius, Alexander (MATEC Web of Conferences)
This paper discusses the influence of joint orientation with non-rotationally symmetric geometry, on load distribution and structural behavior. The focus is on understanding how changes in the alignment of individual joints affect the distribution of load, neighboring joints, and the overall performance of the component. Lap shear specimens with multiple joints arranged in a line are analyzed to explore these effects. Simplified models are used to model the joints in finite element simulations, allowing for efficient yet accurate analysis of the load distribution and structural response under varying joint orientations. Variations in joint orientation result in measurable changes in the distribution of forces on adjacent joints, influencing their behavior and that of the overall assembly. Experimental validation confirms the numerical results, providing deeper insights into the interaction between individual joints and their surroundings. This work contributes to the development of systematic approaches for optimizing the design of components with non-rotationally symmetric joints. The study highlights the importance of considering directional properties of joints in designing structural components.

Impact of the parameter distribution on the predictive quality of metamodels for clinch joint properties - Einwag, Jonathan-Markus; Mayer, Yannik; Goetz, Stefan; Wartzack, Sandro (Materials Research Proceedings)
Abstract. The growing significance of lightweight design, reveals drawbacks of conventional joining processes such as welding, which are known to consume a considerable amount of energy. This fosters the use of mechanical joining processes including clinching. However, the lack of universally applicable design methods results in a cost- and time-intensive design process. The utilization of machine learning methods can overcome these drawbacks. To ensure a reliable clinch joint design, inherent uncertainties of the design parameter such as tool deviations need to be considered in the design process. Varying distributions of design parameters, due to changes in the manufacturing process, can lead to high-computational effort in recalculating the resulting clinch joint properties with numerical simulations. Current metamodel-based methods for consideration of inherent uncertainties within the design parameters do not investigate the transferability of metamodels to different distributions of design parameters, which can lead to incorrect predictions. Therefore, this contribution investigates the performance of several metamodels on differently distributed design parameters. The obtained results indicate that metamodels demonstrate the best performance when training and evaluation distributions are identical and that polynomial regression models perform best on disparate distributions, when trained on uniform distributions.

Implementation and Results of a Multi-Stage Model Predictive Traffic Light Control System - Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (2024 IEEE 27th International Conference on Intelligent Transportation Systems (ITSC))

Improvement of Wind Power Utilization Through Flexible Operation of Data Center in Wind Parks - Ahmadi, Mehdi; Knorr, Lukas; Meschede, Henning (Renewable Energy)

Impulse 7. Texte und Bilder zur Kunstvermittlung. Ein interdisziplinäres Projekt zur Biennale Venedig 2024.

In Likes We Trust oder die unmögliche Möglichkeit vom Like als Gabe zu sprechen - Schulz, Christian (Populäre Artikulationen – Artikulationen des Populären)

In situ computed tomography – Analysis of settling effects during single-lap shear tests with clinch points - Köhler, D.; Troschitz, J; Kupfer, R.; Gude, M. (Materials Research Proceedings)
Abstract. In the field of mechanical engineering, destructive tests such as shear tests of mechanical joints are usually followed by imaging methods such as microsectioning or computed tomography (CT). They can help to interpret the measured load-displacement curves, analyze the failure behavior and validate numerical models. However, due to unloading, springback effects and crack closures can occur, which influence the state of the investigated specimen. In this context, in situ CT is able to explore the testing process with a specimen under load avoiding these influences. For in situ CT investigations, the displacement increase is interrupted at certain stop points. While the displacement is kept constant, the CT scan is performed. However, it was observed that the reaction force reduces during CT scanning, e. g. due to settling effects in the test setup. Although in situ CT is established now in research, little attention is paid to the uncertainties which arise from the discontinuous testing procedure. This study systematically explores the impact of these interruptions on the load-displacement behavior and the geometry of clinch points during tensile shear testing. To quantify the influence of the interruptions, loads at defined displacement levels and the final geometry are evaluated statistically. We found, that the load-displacement behavior of both test groups is similar. Despite some small but significant statistical deviations of the loads and the final geometry, our results show that, discontinuous testing has a high level of significance for the phenomena overserved in shear tests with clinch points.

Incentive-Based Platoon Formation: Optimizing the Personal Benefit for Drivers - Heinovski, Julian; Ergenç, Doǧanalp; Thommes, Kirsten; Dressler, Falko (IEEE Open Journal of Intelligent Transportation Systems)

Increasing the sensitivity of ultrasonic transmission measurements for elastic material parameter estimation - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Claes, Leander; Birk, Carolin; Henning, Bernd (Measurement Science and Technology)
Abstract Ultrasonic transmission measurements can be used for material characterization, as the propagation time of sound waves and thus their velocity depends on the elastic material parameters. Measurement results for the elastic material parameters are acquired non-destructively using ultrasonic transmission measurements of hollow cylindrical polymer specimens. To determine the material parameters, an inverse approach is used comparing measurements with simulated data. Previous studies show that the procedure exhibits low sensitivity with respect to the shear parameters of the material. In order to increase the sensitivity, we propose to apply a spatially annular excitation on the base of the specimen. As a measure to analyse the sensitivities with respect to all parameters and their linear independence, we observe the volume of the parallelotope of the sensitivity vectors. Here, a scaled boundary finite element formulation of wave propagation in the specimen is expanded to yield derivative information directly, and a sensitivity analysis can be carried out efficiently. Finally, the results of this sensitivity analysis with regard to the annular excitation are also applied to the measurement setup.
Keywords: Sensitivity analysis; Ultrasonic transducer; Guided waves; Polymers; Gram determinant

Influence de l'utilisation de la réalité augmentée lors des expériences chimiques sur la connexion des niveaux de représentation dans les explications des élèves - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Actes des XIIIe Rencontres scientifiques de l’ARDIST)

Influence of Liquid metal embrittlement on load-bearing capacity of resistance spot welds under crash loads: A study based on S-Rail components - Yang, Keke; Biegler, Max; Happe, Linus; Striewe, Marius; Olfert, Viktoria; Hein, David; Rethmeier, Michael; Meschut, Gerson (Materials Research Proceedings)
Abstract. Liquid Metal Embrittlement (LME) cracking is a well-documented issue encountered during resistance spot welding (RSW) of zinc-coated advanced high-strength steels (AHSS) in automotive manufacturing. Given that existing research has predominantly focused on laboratory-scale samples and lacks investigation into the load-bearing capacity of joints under crash conditions, this study aims to fill these gaps by analyzing third-generation zinc-coated AHSS. S-Rail components were produced through stamping to replicate real-world manufacturing conditions and geometries of automotive parts. To account for the disturbances typically encountered in production, samples with LME cracks were intentionally fabricated. Subsequently, a modified three-point bending test, assisted by numerical simulations, was developed to effectively apply loads to the weld spots of the S-Rail components. Results from crash tests demonstrated that observed light crack severity does not significantly compromise the joint's load-bearing capacity or lead to earlier joint failure.

Influence of microstructures on liquid spreading on inclined plates: A CFD based study - Dechert, Christopher; Kenig, Eugeny Y. (Chemical Engineering Science)

Influence of pre-shearing on the rheological properties of filled rubber compounds - Kleinschmidt, Dennis; Brüning, Florian (KGK Kautschuk Gummi Kunststoffe)
Keywords: Rheologie; Viskosität; Wandgleiten

Information Circularity Assistance based on extreme data - Gräßler, Iris; Weyrich, Michael; Pottebaum, Jens; Kamm, Simon (at - Automatisierungstechnik)
This paper presents the concept of Information Circularity Assistance, which provides decision support in the early stages of product creation for Circular Economy. Engineers in strategic product planning need to proactively predict the quantity, quality, and timing of secondary materials and returned components. For example, products with high recycled content will only be economically sustainable if the material is actually available in the future product life. Our assumption is that Information Circularity Assistance enables decision makers to incorporate insights from extreme data – high-volume, high-velocity, heterogeneous and distributed data from the product life – into product creation through intelligent Digital Twins. Artificial Intelligence can help to derive sustainable actions in favor of circular products by processing extreme data and enriching it with expert knowledge. The research contributes in three key dimensions. First, a comprehensive literature review is conducted. This review covers concepts of intelligence in Scenario-Technique for strategic product planning, Digital Twin-based analysis of extreme data and relevant technologies from Data Science and Artificial Intelligence. In all areas, the state of the art and emerging trends are identified. Secondly, the study identifies information needs along the steps of the Scenario-Technique and information offerings based on Digital Twins. The concept of Information Circularity Assistance results from the coupling of these demands and offerings, extending the Scenario-Technique beyond traditional expert-based methods. Third, we extend existing Digital Twin methods used in circularity and discuss the deployment of Data Science and Artificial Intelligence algorithms within the product creation process. Our approach uses extreme data to provide a strategic advantage in optimizing product life cycle planning, which is illustrated by two sample applications. The aim is to provide Information Circularity Assistance that will support experienced product planners, developers, and decision makers in the future.
Keywords: Scenario-Technique; Artificial Intelligence; Digital Twin; Large Language Models

Information dissemination and confusion in signed networks - Jin, Ligang; Steffen, Eckhard (Discrete Applied Mathematics)
We introduce a model of information dissemination in signed networks. It is a discrete-time process in which uninformed actors incrementally receive information from their informed neighbors or from the outside. Our goal is to minimize the number of confused actors — that is, the number of actors who receive contradictory information. We prove upper bounds for the number of confused actors in signed networks and in equivalence classes of signed networks. In particular, we show that there are signed networks where, for any information placement strategy, almost 60% of the actors are confused. Furthermore, this is also the case when considering the minimum number of confused actors within an equivalence class of signed graphs.

Innovieren, Transferieren, Gestalten: Eine Wissenschaft, die sich verständigt - Jenert, Tobias (bwp@profil)

Integrating Practice-Based Learning into Formal Education: Stakeholder Perspectives on the Challenges of Learning Location Cooperation (LLC) in Germany’s Dual VET System - Schwede, Jana; Heisler, Dietmar; Harteis, Christian (Social Sciences)

Integration eines Lehrmoduls zur Demokratiebildung in bildungswissenschaftlichen Seminaren der Universität Paderborn - Wehde, Janis (Demokratiebildung als Querschnittsaufgabe der Lehrer:innenbildung)

Integration of multiple-linear and tumbling kinematics into self-piercing riveting - Holtkamp, Pia Katharina; Wituschek, Simon; Lechner, Michael; Meschut, Gerson (MATEC Web of Conferences)
Conventional mechanical joining processes are typically rigid in their tool systems and can only react to changing process and disturbance variables to a limited extent. At the same time, various industries are increasingly trending towards multi-material systems consisting of parts with varying geometric and mechanical properties. Due to the varying properties, rigid mechanical joining processes require sampling procedures and periodic changes of tool components or auxiliary joining parts. Consequently, research is focusing on versatile mechanical joining processes that allow increased control by modifying the process parameters. Two processes based on self-piercing riveting can achieve a significant increase in process influence possibilities through a multi-linear actuator as versatile self-piercing riveting (V-SPR) and a tumbling superimposed actuator as tumbling self-piercing riveting (T-SPR). Initial research into V-SPR has shown that this process can be used to achieve a higher variation in overall package thickness by adapting the rivet geometry and using multiple linear actuators. The T-SPR process also enables increased material flow control by means of targeted compression of the rivet using the tumbling actuator, thereby extending the range of joints that can be manufactured. Based on these two processes, a combination of the two mechanisms of action is to be developed.

Interacting with fallible AI: Is distrust helpful when receiving AI misclassifications? - Peters, Tobias Martin; Scharlau, Ingrid (Frontiers in Psychology)
Due to the application of Artificial Intelligence (AI) in high-risk domains like law or medicine, trustworthy AI and trust in AI are of increasing scientific and public relevance. A typical conception, for example in the context of medical diagnosis, is that a knowledgeable user receives AIgenerated classification as advice. Research to improve such interactions often aims to foster the user’s trust, which in turn should improve the combined human-AI performance. Given that AI models can err, we argue that the possibility to critically review, thus to distrust, an AI decision is an equally interesting target of research. We created two image classification scenarios in which the participants received mock-up AI advice. The quality of the advice decreases for a phase of the experiment. We studied the task performance, trust and distrust of the participants, and tested whether an instruction to remain skeptical and review each piece of advice led to a better performance compared to a neutral condition. Our results indicate that this instruction does not improve but rather worsens the participants’ performance. Repeated single-item self-report of trust and distrust shows an increase in trust and a decrease in distrust after the drop in the AI’s classification quality, with no difference between the two instructions. Furthermore, via a Bayesian Signal Detection Theory analysis, we provide a procedure to assess appropriate reliance in detail, by quantifying whether the problems of under- and over-reliance have been mitigated. We discuss implications of our results for the usage of disclaimers before interacting with AI, as prominently used in current LLM-based chatbots, and for trust and distrust research.
Keywords: trust in AI; trust; distrust; human-AI interaction; Signal Detection Theory; Bayesian parameter estimation; image classification

Interaction- or Material-Centred Implementation of Teacher Professional Development: a Comparison of Teachers’ Competence Development and Potential Lesson Planning Lehrkräftefortbildung interaktions- oder materialzentriert implementieren: Ein Vergleich hinsichtlich der Kompetenzentwicklung sowie der potentiellen Unterrichtsplanung von Lehrkräften - Richter, Alix; Bruns, Julia; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Abstract Teacher professional development (TPD) is a crucial support mechanism for mathematics teachers. Strategies for implementing TPD include disseminating educative curriculum materials or conducting TPD courses. However, it remains unclear whether different implementations of the same TPD support mathematics teachers in distinct ways. This study investigated two implementations of the TPD EmMa-FS which focuses early mathematics education (EME) for German vocational school (VS) teachers who instruct prospective early childhood (EC) educators. One group of teachers received an in-person TPD course along with educative curriculum materials ( n PM = 26), whereas the other received only the educative curriculum materials ( n M = 15). The effects on VS teachers’ beliefs and knowledge concerning EME were examined using a t -test and repeated measures ANOVA. To assess how teachers in the different implementation groups made use of the TPD in their lesson planning, participants submitted hypothetical lesson sequences on early numeracy, which were analysed for instructional quality, covered content, and the visible implementation of the provided educative curriculum materials using qualitative content analysis. The results indicated that both TPD implementations positively affected VS teachers’ knowledge related to EME but not their beliefs. While the instructional quality of the lesson sequences varied across both groups, participants who received the TPD course appeared to use the educative curriculum materials more often and to cover more content.

Interkulturelle Kompetenzen in der Musikwissenschaft. Potenziale hybrider Kooperationsseminare - Adler, Luise (Paderborner Beiträge 2024. die hochschullehre - Themenheft 2025)
Auslandsaufenthalte von Studierenden sind im Fach Musikwissenschaft an der Universität Paderborn eher eine Ausnahme. Das hat unterschiedliche Gründe, unter anderem die nicht vorhandene curriculare Verankerung. Dabei belegen diverse Untersuchungen, dass solche Aufenthalte den interkulturellen Kompetenzerwerb und damit Fähigkeiten fördern, die unabhängig vom Fach in einer globalisierten Welt immer größere Relevanz im Berufsleben einnehmen. Im Projekt wurde ein hybrides internationales Kooperationsseminar entwickelt und durchgeführt sowie in Bezug auf den Erwerb dieser wichtigen Schlüsselqualifikation evaluiert. Die Auswertung der unter anderem durch Fragebögen erhobenen Entwicklung konnte deutlich die positiven Auswirkungen eines hybriden Kooperationsseminars auf interkulturelle Kompetenzen, die Auseinandersetzung mit verschiedensten Aspekten einer anderen Kultur, darunter Geschichte, Politik, (Post-)Kolonialismus und den eigenen Privilegien aufzeigen. Zudem lassen sich aus der Evaluation weitere Ideen für rein digitale Formate ableiten.
Keywords: interkulturelle Kompetenz; interkulturelle Sensitivität; Musikwissenschaft; digitale Lehre; hybride Lehre; intercultural competence; intercultural sensitivity; musicology; digital education; hybrid education

International perspectives and attitudes towards speech and language therapy and multilingualism - Eikerling, Maren; Bloder, Theresa; Castro, Sofía; Rinker, Tanja; Lorusso, Maria Luisa (Clinical Linguistics & Phonetics)

Intrinsic lubrication: A new approach in the context of the deep drawing process - Cakici, Ermir; Homberg, Werner (Materials Research Proceedings)
Abstract. This study presents intrinsic lubrication as a novel approach to deep drawing processes, using additively manufactured, lubricant-permeable tools to minimize lubricant consumption and improve efficiency. Two systems were evaluated: a passive system based on capillary action and gravity, and an active system using pumped delivery for precise, on-demand application. Experimental tests were conducted on micro-bores (0.2-0.5 mm) to demonstrate their suitability for lubricant transport. Smaller bores have excellent capillary action but are prone to clogging, while larger bores offer higher permeability. The passive system is resource-efficient but requires adjustments to counteract gravitational asymmetry. The active system provides consistent lubricant distribution but is more complex. These findings provide a basis for optimizing intrinsic lubrication systems.

Intrinsic production of metal-carbon fiber reinforced plastic hybrid shafts using vacuum-assisted resin transfer molding - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Ellouz, Manel; Kordisch, Thomas (Journal of Composite Materials)
Over the past decades, the importance of lightweight structures in the aircraft and automotive industries has steadily increased due to regulations aimed at reducing global warming. Work hardened steel alloys are commonly used for lightweight applications, but they face stability issues when the material thickness reaches certain thresholds. Fiber Reinforced Plastics (FRP) offer a viable alternative due to their high strength-to-weight ratio, but they are often expensive due to long production cycles and high material costs. A feasible solution lies in hybrid lightweight designs that utilize expensive FRP materials only in highly stressed areas, achieving a balance between low mass and acceptable cost. These hybrid structures are lighter than metal components and more cost-effective compared to fully FRP structures, without compromising mechanical properties. This study focuses on producing rotationally symmetrical hybrid structures using Resin Transfer Molding (RTM) combined with vacuum assistance in a single-stage process. The research examines the effects of injection pressure, mold temperature, and the interface between metal and FRP. The mechanical characterization of these hybrid structures was conducted to assess their performance under torsion, compression, and interlaminar shear strength (ILSS) loading conditions. The results indicate that hybrid designs can offer a lightweight alternative without compromising mechanical properties.

Introduction to the Ethics of Emerging Technologies - Reijers, Wessel; Thomas Young, Mark; Coeckelbergh, Mark

Investigating the kill cloud: information warfare, autonomous weapons & AI - Bhila, Ishmael (Digital War)
The “kill chain”—involving the analysis of data by human users of military technologies, the understanding of that data, and human decisions—has fast been replaced by the “kill cloud” that necessitates, allows, and exacerbates increased thirst for domination, violence against distant populations, and a culture of experimentation with human lives. This commentary reports an interdisciplinary discussion organised by the Disruption Network Lab that brought together whistleblowers, artists, and experts investigating the impact of artificial intelligence and other emerging technologies on networked warfare. Exposing the problematics of networked warfare and the kill cloud, their colonial overtones, effects on human subjects in real life, erroneous scientific rationalities, and the (business) practices and logics that enable this algorithmic machinery of violence. The conference took place from the 29th of November to the 1st of December 2024 at the Kunstquartier Bethanien in Berlin, Germany.
Keywords: autonomous weapons systems; algorithmic warfare; cloud computing; war on terror

Investigation failure behavior in the shear tensile test with respect to the arrangements of clinched joints - Wolf, Eugen; Brosius, Alexander (Materials Research Proceedings)
This paper focuses on the failure behavior of specimens with various configurations of clinched joints under shear tensile loading. The primary objective is to assess the influence of the joining direction and the spatial arrangement of clinched joints on their mechanical performance. A number of experiments was conducted, focusing on three clinched joints arranged in different configurations, each varying in terms of joining direction and spacing. These configurations were subjected to shear tensile tests, with force-displacement curves recorded for each sample to provide a detailed characterization of their structural response. The experimental findings indicate that the specific arrangement of the clinched joints, in terms of joining direction, has a marginal impact on the overall failure behavior. This suggests that intricate modifications to the joining direction are unnecessary to achieve improved mechanical performance in such applications. These results offer valuable insights for the design of clinched joint assemblies, indicating that simplified joining strategies may suffice without compromising structural integrity under shear loading.
Keywords: Joining; Sheet Metal; Clinching

Investigation failure behavior in the shear tensile test with variety of specimen stiffness - Wolf, Eugen; Brosius, Alexander (MATEC Web of Conferences)
This paper focuses on the failure behavior of clinched specimens with various stiffnesses under shear tensile loading. The primary objective is to assess the influence of the specimen stiffness with an arrangement of clinched joints. The specimen stiffness depends on several variables. In addition to the material selection, the specific choice of geometry and the design of the clinched joints must also be taken into account. A number of experiments was conducted to investigate the failure behavior of specimens with an arrangement of three clinched joints under shear tensile loading. These configurations were subjected to shear tensile tests, with force displacement curves recorded for each specimen to provide a detailed characterization of their structural response. The stiffness is modified by altering the specimen width, which has marginal impact on the maximum force. The experimental findings indicate that reducing the specimen stiffness results in a shift in the type of stress, with the failure behavior becoming increasingly influenced by bending stress. These results offer important insights for the design of clinched joint assemblies, indicating that it is feasible to achieve the desired properties by changing the specimen stiffness.
Keywords: Joining; Sheet Metal; Stiffness; Clinching

Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

Is Tax Transfer Pricing Harmonization a Panacea? Real Effects of Global Tax Transparency and Standards Consistency - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren (The Accounting Review)

Islam II - Paul, Jürgen; Schneider, Irene; Kokew, Stephan; Malik, Jamal; Schulze, Fritz; Günther, Sebastian; Schrode, Paula; Rebstock, Ulrich; Gharaibeh, Mohammad; Würsch, Renate; Rudolph, Ulrich; Reichmuth, Stefan; et al.

Kausalität im Längsschnitt. Funktionen und Formen von weil, denn, deshalb, deswegen, nämlich und da in der Textproduktion vom 4. bis zum 6. Schuljahr - Topalovic, Elvira; Drepper, Laura; Blachut, Alisa (Semantische Phänomene lehren und lernen. Linguistische Berichte (LB))

KI außer Kontrolle - Hälterlein, Jens (AUSDRUCK - Das IMI-Magazin)

Kinder- und Jugendtheologie und Tradition. - Reis, Oliver (Was hat das mit zu tun? Zugange zur Tradition in der islamischen Religionspädagogik)

Kinderlyrik als soziale Praxis am Beispiel von Arne Rautenbergs Lyrikbänden Mut ist was Gutes (2023) und Sekundenfrühling (2023) - Jagdschian, Larissa Carolin (Arne Rautenbergs und die (Kinder-)Lyrik der Gegenwart)

Klagende Robben. Environmental Sound Art und das Problem der Anwaltschaft - Spieker, Jonas (Non*binär! Sound und Gender im Posthumanismus)

Kollegiales Feedback in der Hochschullehre - Osthushenrich, Judith (Praxishandbuch Hochschullehre II - Bewertung, Digitalisierung und Barrierefreiheit)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Kölner Vorherrschaft über Westfalen? Zu den Ambitionen der Erzbischöfe von Köln (1188–1220) - Schreckenberg, Carolin (775 – Westfalen. Das Buch. Eine Region wird gemacht)

Kommunale Wasserregime - Wasser und Macht in der europäischen Stadt 1300-1900

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Konzept und Wirkungen eines Lehrmoduls zur demokratischen Erarbeitung von Beurteilungskriterien in bildungswissenschaftlichen Seminaren des Lehramtsstudiums - Wehde, Janis

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Krisen historischen Lernens. Zum historischen Lernpotenzial sprachlich-interaktionaler Krisen im Geschichtsunterricht. - Pilz, Franziska (Theorie und Empirie - ein unzertrennliches Paar? Tagung der Early Career Researcher der Konferenz für Geschichtsdidaktik in der Universität Bielefeld 2023)